Engineering Modeling of Human Cardiovascular System - Lefta Mossa, Hassanain Ali (Nahrain University College of Engineering Journal, 2008)
Cardiovascular system is primarily considered as the human body's transport system. Oxygen, carbon dioxide, nutrients and other vital substances to the various tissues of human body are carried by the blood which circulates in a closed circulation. The cardiovascular system has been comprised of a combination of several basic compartments, which are structurally connected to and functionally interact with each other. Engineering modeling of such important system has become a useful tool to diagnose the cardiovascular diseases and recommend the appropriate way of their medical treatment. This paper presents a quantified model describing the relationship between the input and output variables of the hemodynamic regulation of the system through implementing a set of first order differential equations that governing this performance and describing its parameters such as pressures, volumes and flows in a closed-loop lumped system. Construction of this model was based on the interaction between the pulsating heart and the vascular circulations of the system through mapping the physiological parameters to the electrical analog elements (resistor, capacitor and inductor and diode) depending upon the close correspondence between the electrical circuits and the cardiovascular system in order to obtain a reasonable investigation for the behavior of the system in normal and pathophysiological condition